Evaluation of the learning process of informational competencies in university students - Jorge Espinoza-Colón; Luis Medina-Gual (Universidad de Guadalajara, 2021)
This article aims to present the results of a study on the learning process of informational competence in the Universidad José Vasconcelos, Oaxaca, Mexico. From a qualitative research approach, semi-structured interviews, and requests for drawings were applied, and non-participant observation of six students' information search practices was carried out. The findings made it possible to identify quantitative and qualitative changes in the declarative, procedural and attitudinal components of the competence, which differentiate three levels of performance: low, medium, and high. The critical element to understand the competence learning process is in its attitudinal component since this determines the amount and type of declarative knowledge, as well as the procedures that the student is willing to deploy in a coordinated way to search, evaluate and use the information to achieve your academic goals.